Analyze of the Model for Cancer Transmission - Alongkot Suvarnamani; Puntani Pongsumpun (My University, 2021)
Article Analyze of the Model for Cancer Transmission Share on Authors: Alongkot Suvarnamani King Mongkut's Institute of Technology Ladkrabang, Thailand King Mongkut's Institute of Technology Ladkrabang, ThailandView Profile , Puntani Pongsumpun King Mongkut's Institute of Technology Ladkrabang, Thailand King Mongkut's Institute of Technology Ladkrabang, ThailandView Profile Authors Info & Claims IPMV 2021: 2021 3rd International Conference on Image Processing and Machine Vision (IPMV)May 2021 Pages 77–81https://doi.org/10.1145/3469951.3469965Online:21 August 2021Publication History 0citation9DownloadsMetricsTotal Citations0Total Downloads9Last 12 Months9Last 6 weeks1 Get Citation AlertsNew Citation Alert added!This alert has been successfully added and will be sent to:You will be notified whenever a record that you have chosen has been cited.To manage your alert preferences, click on the button below.Manage my AlertsNew Citation Alert!Please log in to your account Save to BinderSave to BinderCreate a New BinderNameCancelCreateExport CitationPublisher SiteGet Access
Keywords: RNA Interference and Gene Delivery; Immunotherapy and Immune Responses; Phagocytosis and Immune Regulation